The contemporary look at the problem of recognizing and diagnosing postmenopausal osteoporosis and eliminating the risk of a fall - Janiszewska, Mariola; Kulik, Teresa Bernadetta; Dziedzic, Małgorzata Anna; Żołnierczuk-Kieliszek, Dorota (Menopause Review/Przegląd Menopauzalny, 2014)
Osteoporosis constitutes a relevant health, social and economic problem of the contemporary world. As a chronic disease, often nicknamed the “silent thief”, it is an object of the clinical research and a reason for many ambiguities. The most noticeable and basic symptom of osteoporosis is a low-energy fracture, which brings pain, physical disability, and a noticeable decrease in one’s quality of life. Osteoporosis affects the entire population; however, women in the postmenopausal period and the elderly are mostly exposed to its progress. The risk of falling ill concerning women simply grows with the age and doubles with every decade after the age of 65. It is estimated that osteoporosis affects 200 million women worldwide, and about 20-25% of them will sustain an injury in the form of a bone fracture. In Poland, the problem of osteoporosis concerns 2.4 million women. The article attempts to show current views on examining and diagnosing postmenopausal osteoporosis and prevention of the fall risk. The BMD (bone mineral density) is considered the basis of osteoporosis diagnosis in postmenopausal women as well as an absolute 10-year risk of fractures and experienced osteoporotic fractures. All people at an increased fall risk should be provided with the multifactorial programme of fall prevention.